PREVALENCE OF METABOLIC SYNDROME AMONG PATIENTS WITH SCHIZOPHRENIA FROM LONG CARE UNIT IN FORENSIC PSYCHIATRY PROGRAM: AN OBSERVATIONAL STUDY - Siddiqui, Javed Ather; Qureshi, Shazia Farheen; Alotaibi, Hani Matrok; Alkhammash, Waleed Mohsen (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Metabolic syndrome is a leading health concern among schizophrenia patients treated with antipsychotics. The morbidity and mortality rates of these patients can increase when they already have cardiovascular disease and other risk factors. This study aimed to examine the prevalence of metabolic syndrome and its relationship to various clinical parameters such as blood pressure, fasting blood glucose, triglycerides, high-density lipoprotein, and waist circumference. Methods – This disease-oriented observational study was carried out in the forensic psychiatric rehabilitation ward at the Erada & Mental Health Complex - Taif, Saudi Arabia. Patients admitted to the inpatient ward between 2018 and 2023 participated in the study (N = 71). The relationship between metabolic syndrome and psychotropic medications was also examined. Schizophrenia was defined by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5-TR) criteria. Metabolic syndrome was assessed based on the international criteria National Cholesterol Education Program’s Adult Treatment Panel III report (ATPIII) criteria and AHA/NHLB. Results – In this study, 71 volunteer schizophrenic patients were included, and an observational study over five years was conducted. We found the total number of metabolic syndrome patients was 40 (56.34%) compared with 31 (43.66%) patients without metabolic syndrome. The majority of metabolic syndrome patients (57.50%) were aged 41 to 50. The highest number of patients suffering from metabolic syndrome are those taking atypical antipsychotic medications. Among antipsychotic medications, aripiprazole was found the maximum number of 10 (25%) followed by olanzapine 7 (17.5%). Maximum number of metabolic syndrome parameters increased fasting blood sugar 26 (65%) followed by increased body mass index 21 (52.5%). Discuss – This research can contribute to the study of the prevalence of metabolic syndrome among patients with schizophrenia. In the present study, the prevalence of metabolic syndrome was 56.34 percent in schizophrenia. There are several metabolic side effects associated with second-generation antipsychotics and if these aren't treated properly, they can lead to serious health complications, such as diabetes, dyslipidemia, and fatal heart disease. Conclusion - In our study, metabolic syndrome was most prevalent among patients between 41 - 50 years of age. Therefore, clinicians are encouraged to screen and monitor metabolic syndrome and treat cardio-metabolic risk factors for optimum long-term management.  Keywords: schizophrenia, metabolic syndrome, antipsychotics.